2020
DOI: 10.1002/9781119508229.ch13
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Na‐Ca Carbonates in the Deep Carbon Cycle

Abstract: Carbonates play a central role in the subduction transport of oxidized carbon from Earth's surface to the deep mantle. The melting of carbonated rocks also leads to the release of carbonate melts, regarded as important oxidizing and metasomatizing agents, from the subducting slab. Although at upper mantle conditions the chemistry of carbonates within the subducting slab is restricted to the thoroughly studied ternary CaCO 3 -MgCO 3 -FeCO 3 system, recent experimental and natural evidences strongly suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…The proposed hypotheses are consistent with recent studies on the HP behavior of Na-Ca carbonates (Grassi and Schmidt, 2011;Kiseeva et al, 2013;Litasov et al, 2013Borodina et al, 2018Vennari et al, 2018;Rashchenko et al, 2020) that have already suggested an important variety of Na-Ca double carbonates in the system Na2CO3-CaCO3 at HP-HT, linked each other by a sequence of decomposition reactions (Rashchenko et al, 2020), as well as the existence of high-pressure polymorphs of Na2Ca2(CO3)3-shortite. As a consequence, the stability/decomposition reactions occurring in the mentioned phases during decompression are a fundamental constraint for the CO2 release from mantle-derived magma, which can be expected to influence magma viscosity and eruption explosivity (Allison et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The proposed hypotheses are consistent with recent studies on the HP behavior of Na-Ca carbonates (Grassi and Schmidt, 2011;Kiseeva et al, 2013;Litasov et al, 2013Borodina et al, 2018Vennari et al, 2018;Rashchenko et al, 2020) that have already suggested an important variety of Na-Ca double carbonates in the system Na2CO3-CaCO3 at HP-HT, linked each other by a sequence of decomposition reactions (Rashchenko et al, 2020), as well as the existence of high-pressure polymorphs of Na2Ca2(CO3)3-shortite. As a consequence, the stability/decomposition reactions occurring in the mentioned phases during decompression are a fundamental constraint for the CO2 release from mantle-derived magma, which can be expected to influence magma viscosity and eruption explosivity (Allison et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…providing evidences for a likely sublithospheric mantle origin for alkaline ultramafic magmas and extrusive carbonatites (Humphreys et al, 2010). The solubility of Na in the structure of aragonite might be drastically increased through the formation of nano lamellae of HP polymorph of Na2Ca(CO3)2 giving rise to what has been recently called "Na-aragonite" (Rashchenko et al, 2020). Our hypothesis about formation of modular structures between the HP form of Na2CO3 and aragonite at HP is supported by the amount of dissolved Ca 2+ in the structure of Na2CO3 up to 15% (Podborodnikov et al, 2018), which cannot be explained with isomorphism as the authors suggested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Исследования фазовых диаграмм двойных карбонатов при высоких давлениях позволяют выявить ряд новых фазовых состояний кристаллов [11], которые еще предстоит открыть [12]. Поэтому структурные свойства двойных кристаллов под давлением изучались с помощью синхротронного излучения в [13], где показано, что сжимаемость карбонатов калия (натрия)-магния ниже, чем у магнезита и доломита, а K 2 Mg(CO 3 ) 2 переходит в моноклинную полиморфную форму при 8.05 GPa.…”
Section: Introductionunclassified